Drying characteristics of sweet cherry - Doymaz, Ibrahim; Ismail, Osman (ELSEVIER, 2011)
The effects of alkali emulsion of ethyl oleate and air temperature (60, 70 and 75 degrees C) on the drying characteristics of sweet cherry were studied using a hot air dryer at a constant air velocity of 2.0 m/s. It was observed that both the alkali emulsion of ethyl oleate and air temperature affected the drying time. The drying times of pre-treated samples were 19.5-22.6% shorter than those of control samples. Five semi-theoretical thin-layer models, namely, Lewis, Henderson and Pabis, Logarithmic, Page, Wang and Singh models were used for the modeling of the drying kinetics. The fit quality obtained with each model was evaluated using statistical tests. After comparing experimentally obtained values with the calculated values from the models, it was concluded that Page model represents the drying characteristics better than the other models. The effective moisture diffusivity was determined by using Fick's second law and was observed to lie between 5.683 x 10(-10) and 1.544 x 10(-9) m(2)/s for the pre-treated and control samples. Rehydration ratio was significantly affected by pre-treatment and air temperature. It was found to increase proportionally with the increase in air drying temperature. (C) 2010 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Sweet cherry; Drying; Mathematical models; Pre-treatment solution; Rehydration ratio; WATER DIFFUSIVITY; AIR-TEMPERATURE; KINETICS; PRETREATMENTS; QUALITY; SLICES; DEHYDRATION; PARAMETERS; MODELS; GRAPES; Biotechnology & Applied Microbiology; Engineering; Food Science & Technology